2015
DOI: 10.4103/0972-0707.153068
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of apical seal obtained after irrigation of root end cavity with MTAD followed by subsequent retrofilling with MTA and Biodentine: An in vitro study

Abstract: Introduction:The present study is designed to assess the apical seal obtained after root end cavity irrigation with MTAD and retrograde filling with mineral trioxide aggregate (MTA) and Biodentine.Materials and Methods:Sixty extracted maxillary central incisors were instrumented and obturated. Apical 3 mm of all the roots were resected and retrograde preparations of 3 mm were made in all the teeth using ultrasonic tips. Thirty root end preparations were irrigated with MTAD for 5 min (Group 1), while 30 were ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
3
12
0
2
Order By: Relevance
“…However, in this study the least microleakage was exhibited by Biodentine although the difference was not statistically significant. The result of our study is in concurrence with the study conducted by Khandelwal A et al [23], Radeva E et al [24], Naik MM et al [25], Kokate SR et al [8] Comparing the sealing ability of MTA and Biodentine as root-end filling material Khandelwal A et al [23] concluded that Biodentine can be used as a replacement for MTA. The study by Radeva E et al [24] concluded that Biodentine can be more effective as apical sealing material compared to MTA.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, in this study the least microleakage was exhibited by Biodentine although the difference was not statistically significant. The result of our study is in concurrence with the study conducted by Khandelwal A et al [23], Radeva E et al [24], Naik MM et al [25], Kokate SR et al [8] Comparing the sealing ability of MTA and Biodentine as root-end filling material Khandelwal A et al [23] concluded that Biodentine can be used as a replacement for MTA. The study by Radeva E et al [24] concluded that Biodentine can be more effective as apical sealing material compared to MTA.…”
Section: Discussionsupporting
confidence: 91%
“…The study by Radeva E et al [24] concluded that Biodentine can be more effective as apical sealing material compared to MTA. Naik MM 25 concluded that the apical seal obtained with Biodentine was superior to that obtained with MTA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical smear layer in endodontics is defined as a smear layer, which contains microorganisms and necrotic pulpal tissues which is formed on the dentinal surfaces, cut by the instruments during apicoectomy and retrograde cavity preparation. 21 Citric acid, EDTA, 35% orthophosphoric acid and BioPure MTAD™ (mixture of tetracycline isomer, acid and detergent) have been recommended for the removal of surgical smear layer but in our study no attempt was done to remove it as the retrograde cavity was just irrigated with normal saline. The thickness of the smear layer is also affected by type of the bur used.…”
Section: Discussionmentioning
confidence: 84%
“…En estudios más recientes como los realizados por Cárdenas S. en el año 2017 (11) , Ravichandra P. et al en el año 2014 (23) , Naik M et al en el año 2015 (20) y Nanjappa A. et al en el año 2015 (22) concluyeron que el Biodentine era más eficaz que el MTA. A diferencia de los resultados d este estudio donde el MTA se posiciona con el mayor nivel de eficacia, esto podría deberse a que el MTA surgió antes que el Biodentine y por ende, se lo estudió en más investigaciones.…”
Section: Eficacia Comparadaunclassified